Evaluation of HLA-G 14-bp ins/del and +3142G>C polymorphisms with susceptibility to recurrent spontaneous abortion - Mohammad Hashemi; Mojgan Mokhtari; Safura Khazaeian; Gholamreza Bahari; Maryam Rezaei; Alireza Nakhaee; Mohsen Taheri (Elsevier, 2017)
Objective: HLA-G is critically important for successful implantation during pregnancy. Increasing evidence supposed that HLA-G plays a key role in tolerance of the semi-allogeneic graft in pregnancy by inhibiting the cytotoxic functions of T and NK cells. The present study aimed to evaluate the impact of HLA-G rs1063320 (+3142G>C) and 14-bp insertion (ins)/deletion (del) polymorphisms on recurrent spontaneous abortion (RSA). Materials and Methods: Genomic DNA from 93 RSA patients and 93 normal fertile women was isolated using the salting out method. Genotyping of HLA-G +3142G>C and 14-bp ins/del variants was done by polymerase chain reaction restriction fragment length polymorphism (PCR-RFP) and PCR method, respectively. Results: The HLA-G +3142G>C polymorphism increased the risk of RSA in codominant (OR = 2.39, 95%CI = 1.27-4.49, p = 0.010, GC vs GG; OR = 3.28, 95%CI = 1.16-9.72, p = 0.040, CC vs GG) and dominant (OR = 2.52, 95%CI = 1.37-4.64, p = 0.004, GC + CC vs GG) tested inheritance models. HLA-G rs1063320 C allele was associated with increased risk of RSA (OR = 1.84, 95%CI = 1.20-2.83, p = 0.007). The del/del genotype as well as del allele of 14-bp ins/del variant increased that risk of RSA (OR = 3.02, 95%CI = 1.23-7.41, p = 0.025 and OR = 1.65, 95%CI = 1.09-2.50, p = 0.022, respectively). Conclusion: In summary, our results showed that HLA-G gene polymorphisms significantly increased the risk of RSA in a sample of the Iranian population.